A Study on the Quality of Campus Landscape on Students' Attendance at the University Campus - Mojgan Ghorbanzadeh (Salehan Institute of Higher Education, 2019)
Considering the expansion of higher education program in Iran to meet the needs of youth in recent years, there have been many institutes of higher education in closed spaces. This need is balanced now and it is time to highlight the importance of the impact of open spaces on higher education and improving its quality. The purpose of this study is to review landscape designing theories in University of Bojnord and investigating the role of these components in students’ attendance in the university environment. The ultimate goal is to extract and prioritize the desirability factors of the open spaces of campus and the students' attendance at the university. -The findings of the extraction have been analyzed based on the access to landscape design patterns. It is conducted by designing a visual questionnaire based on the components of landscape desirability such as understanding, exploration, compatible with the desire for participation and relaxation and enjoyment of the landscape. The questionnaire was given to 55 Students of University of Bojnord. The statistical population was all students of University of Bojnord. The sampling method was random clustering from the faculties of based on their gender and major. The data was stored, analyzed and processed in SPSS software. Data analysis shows the priority of the main factors of the desirability of open spaces on campus. The landscape desirability of Bojnurd University and students’ attendance at university is low and it requires a serious review of the architectural design of the university landscape.